Comparing thermal discomfort with skin temperature response of lower-limb prosthesis users during exercise. (October 2019) - Diment, Laura E.; Thompson, Mark S.; Bergmann, Jeroen H.M.
Abstract: Background: Thermal discomfort is prevalent among prosthesis users. This observational study of thirty unilateral lower-limb prosthesis users compared their skin temperatures and the thermal discomfort experienced during exercise between their residual and contralateral limbs. Methods: Participants performed a 2-minute interval cycling exercise test. Skin temperature was measured at matched locations on each leg during the 1-minute rest intervals. Average rate-of-change in skin temperature was compared between legs using a repeated measures analysis of variance. Participants rated thermal discomfort on each leg before and after exercise, and a Wilcoxon signed-rank test was used to compare legs. Ordinal regression evaluated the relationship between the rate-of-change in temperature on the residual limb and the perceived thermal discomfort. Findings: After exercise, thermal discomfort ranked higher on the amputated side ( P = 0.007). On average, both legs cooled during exercise ( P = 0.002), but the difference between legs was not significant. The rate-of change in skin temperature on the residual limb during exercise did not relate to the thermal discomfort experienced (odds ratio of 0.357). Interpretation: These findings indicate that in this patient population, skin temperature does not explain the thermal discomfort experienced, and subjective thermal discomfort is inadequate for detecting thermoregulatory issues, with potential implications for long-term tissue health. Highlights: After exercise, thermal discomfort was substantially greater on the amputated leg. Skin temperature did not explain the thermal discomfort experienced. The skin on both legs cooled during intermittent exercise. The rate of temperature change differed between front and back of the leg. Above-knee amputees rated thermal discomfort higher than below-knee amputees did.